Identifying Gay Behavior Through Guidance and Counseling Module For Senior High School Students - Gusnaldi Gusnaldi; Mudjiran Mudjiran; Afdal Afdal (Global Econedu, 2020)
Homosexuality is defined as romantic attraction, sexual attraction, or sexual behavior between the same sex or gender. Gay is one of the sexual disorders where man is attracted to other straight or gay man. Mostly, teenagers are unaware of this current emerging phenomenon. So, some may get involved or even dragged into this crisis which will lead them to miserable mental state. Their lack of knowledge about the concept and detrimental effect of gay behavior is also the main concern. Hence, a preventive approach should be taken to hinder teenagers, especially male students, from the negative outcome of gay behavior through guidance and counselling program. The paper followed the procedure in descriptive research design. The research population was all public high school students in Padang and there were 100 respondents which was chosen through purposive sampling. Based on the research findings, 15 students (15%) responded in the highest scale, extremely concerned. 23 students (23) were moderately concerned. 58 students (58%) seemed in uncertainty. 4 students (4%) were at loss or slightly concerned facing this crisis. In brief, most students had low awareness of this crisis. Thus, their understanding in gay behavior must be enhanced. The aid offered to help them protect themselves is providing information about the concept of gay behavior, gay characteristics, the causes of gay behavior, the impact of being a homosexual man and how they find a sexual partner through guidance and counseling program.